USE OF WHATSAPP IN LEARNING SITUATIONS: PERSPECTIVES OF STUDENTS OF THE AFRICAN LASALLIAN CENTER (CELAF) - (:unkn) unknown (My University, 2022)
The purpose of this study is to analyze the perception of CELAF students on the use of the social network WhatsApp in the learning activity. The data was collected through a questionnaire and semi-structured telephone interviews, following a mixed methodology. The results show that the WhatsApp social network is positively perceived by the students as a technological tool favorable to learning. They consider it easy to use and affirm that it participates in the improvement of collaborative work between peers. But, the main difficulty in using it is the problem of internet connection.
Keywords: African Research